MANAJEMEN KEPATUHAN DIET GUNA MENINGKATKAN KUALITAS HIDUP PASIEN DIABETES MELLITUS TIPE 2 - Nurhidayah, Titis; Diani, Noor; Agustina, Rismia (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2019)
Diabetes mellitus type 2 is the occurrence of hyperglycemia due to insulinresistance, the primary goal of treatment is through dietary adherence. Thequality of life is important in health, and as the ultimate goal of healthintervention. The aim of this study to analyze the relationship between dietcompliance and the quality of life diabetes mellitus type 2 in Ratu ZalechaHospital Martapura. The design of this study was correlation. There were 37respondents took as samples with accidental sampling, then the data analysis wasdone by using chi-square test. The study instrument used dietary compliancequestionnaires and WHOQOL-BREF. The result analysis obtained significantvalue p=0,028 < 0,005, so H0 rejected. Furthermore, there was a relationshipbetween quality of life and dietary adherence of diabetes mellitus type 2. This wasindicates that the level of dietary adherence can effect quality of life the patientsdiabetes mellitus type 2 in Ratu Zalecha Hospital Martapura.